Leucothoe kawesqari, a new amphipod from Bernardo O'Higgins National Park (Chile), with remarks on the genus in the Magellan Region (Crustacea, Peracarida) - Esquete, Patricia (2017)
Although the genus Leucothoe has been reported repeatedly in the Magellan Region, the citations in the Channels and Fjords Ecoregion were either unidentified or attributed to the previously considered cosmopolitan Leucothoe spinicarpa. In this work, Leucothoe kawesqari sp. n. is described, which can be distinguished from other species of the genus in the Southern Ocean by having eyes present, epimeral plates with no setae, anterior coxae not acutely produced or excavate, coxa 5 slightly bilobed, accessory flagellum present, mandibular palp article 3 shorter than ½ article 2, pereopods 5–7 basis expanded, ovoid, posterior margin weakly crenulate and telson apex irregularly truncated. The new species was found in hard substrates, both unvegetated and with macroalgae, mainly in kelp forest of Macrocystis pyrifera.